Overlooking Feigning Behavior May Result in Potential Harmful Treatment Interventions: Two Case Reports of Undetected Malingering. Issue 4 (23rd March 2020) - van der Heide, Douwe; Boskovic, Irena; van Harten, Peter; Merckelbach, Harald
Abstract: Clinicians tend to overestimate their ability to recognize feigning behavior in psychiatric patients, especially if it concerns patients who have been admitted for observation. Feigning can be either externally motivated (e.g., for financial compensation, known as malingering) or internally motivated (e.g., to assume the "sick role, " known as factitious disorder). Persistent presentation of severe symptoms is usually associated with the factitious disorder. We present two patients with strong external incentives who consistently and convincingly feigned severe psychiatric symptoms during a protracted period of inpatient observation in a specialized center; both were engaged in a procedure for medical asylum. The first case presented with the clinical picture of a psychotic depression with severe motor symptoms, and the second case showed symptoms of a chronic post‐traumatic stress disorder with secondary psychotic symptoms. Both cases were thoroughly investigated but feigning was overlooked, and unnecessary and harmful treatment interventions were given. To prevent iatrogenic damage, we recommend a critical attitude that takes malingering as an option into account in settings where patients are often involved in high stake legal procedures. A clinical sign that might indicate feigning is therapy‐resistant symptoms. To rule out feigning a comprehensive, multimethod approach is required, but an active stance toward collateral information is essential. Specialized psychological tests may be useful for preliminary screening, but for their use in culturally diverse populations as in refugee mental health more research is needed.